(untitled) (ENTHYMEMA, 2021)
This essay examines the influence of Plutarch’s Life of Brutus on Mary Shelley’s Frankenstein, arguing that the relationship between Brutus and his «evil genius» provides Shelley with a model for characterizing the pair of Victor Frankenstein and his Creature. By considering the broader context of Plutarch’s reception from the sixteenth through the early nineteenth centuries, and particularly the construction of Brutus as a ghost-seer, a clinical obsessive, or a revolutionary icon, the essay examines the Brutus/Victor parallel as actual and/or symbolic parricides, shedding new light on Shelley’s failed representation of the French Revolution in her novel.